Equivalent phase current harmonic elimination in quadruple three-phase drives based on carrier phase shift method - Wang, Xuchen; Yan, Hao; Buticchi, Giampaolo; Gu, Chunyang; Zhang, He (MDPI, 2020)
Multiphase drives are entering the spotlight of the research community for transportation applications with their high power density and the possibility of high fault tolerance. The multi three-phase drive is one of the main types of multiphase drives that allows for the direct adoption of commercial three-phase converters and high control flexibility. The elimination of high-frequency current harmonics will reduce the flux linkage harmonics, torque ripple, vibration and noise in machine drives. Therefore, this work introduces a new method to the modelling of equivalent phase current in multi three-phase drives with the double integral Fourier analysis method. A new carrier-based pulse-width modulation (CPWM) method is introduced to reduce the equivalent phase current harmonics by applying proper carrier phase angle to each subsystem in the multi three-phase drives. The proposed angles of carrier signals are analyzed for quadruple three-phase drives, and the corresponding experimental results confirm the significance of the proposed phase-shifted CPWM method to eliminate the equivalent phase current harmonics.